Gershom Scholem and the mystical dimension of Jewish history - Dan, Joseph, 1935-2022 (Modern Jewish masters series, 1987)
""An excellent overview of the history of Jewish mysticism from its early beginnings to contemporary Hasidism ... scholarly and complex."" #x97; Library Journal ""An excellent work, clear and solidly documented by Joseph Dan on Gershom Scholem and on his work."" #x97; Notes Bibliographiques ""An excellent guide to Scholem's work."" #x97; Christian Century.